Physico-Chemical, Antioxidants and Structural Changes During Development of Red-Fleshed Dragon Fruit (Hylocereus Polyrhizus) - Jamaludin, Nur Adilla (2010)
A study was conducted on the changes in physico-chemical, antioxidant content and cellular structures of red-fleshed dragon fruit at every 5 days interval starting from 5 until 35 day after pollination (DAP). The experiment was conducted using randomized complete block design with four replications. Three fruits per replicate were used. Data from measurements of length, diameter, stomatal density, peel and pulp fresh and dry weight, moisture content, ethylene and carbon dioxide rate, pulp firmness, soluble solids concentration (SSC), titratable acidity, pH, peel and pulp betacyanin content and chlorophyll content were analyzed using analysis of variance and differences between means were determined by Duncan’s New Multiple Range Test. Peel and pulp L*, C* and h° values were determined by regression. Correlation carried out using Pearson’s correlation coefficient. Fruit colour changes and cellular structure were documented as photographs and micrographs, respectively. In this study, fruit were non-climacteric with no respiration and ethylene peaks were observed. A decrease in stomatal density with closed stomata was found throughout fruit development and maturation. The moisture content in peel increased, while decreased in pulp was observed as DAP progressed. Colour changes of red-fleshed dragon fruit in pulp occur earlier than the peel. The manifestations of red-violet betacyanin only appear after seeds have matured, then followed by pulp colour changes and finally peel change from green to red-violet. The red-violet betacyanin manifested itself gradually in pulp at 25 DAP followed by peel at 30 DAP. The high retention of betacyanin content during development and maturation had caused it to correlate significantly with soluble solids concentration as in process of betacyanin synthesis, sugar derivatives was needed to form red-violet betacyanin. Titratable acidity and pH in fruit were not correlated with betacyanin content in peel but titratable acidity significantly correlate with betacyanin content in pulp. There were significant relationship between DAP with L*, C* and h° value of peel and pulp. Betacyanin determination using reversed-phase HPLC-photodiode array detection, was confirmed betanin and isobetanin in the fruit. Fruit has high content of antioxidant activity, yet relatively low levels of ascorbic acid and total phenolic contents. This suggest that major source of antioxidant activity of fruit may not contributed from ascorbic acid or phenolics but rather from betacyanin. The developmental processes of fruit were examined using scanning electron microscope (SEM). As DAP progressed, parenchymatous cell lose their integrity due to cell hydrolysis which leads to losing of firmness. The SEM micrographs had revealed that starch granules in pulp decreased in size and intensity as DAP progressed. The degradation of starch granules contribute to softening of pulp tissue. Various form and shape of crystals such as raphides and druses were observed in scale tissues. It is clear, the physico-chemical and betacyanin accumulation of red-fleshed dragon fruit changed as fruit developed, matured and ripened which coincide with structural changes.